New relativistic traversable wormholes and energy constraints in the rastall teleparallel gravitational paradigm - Saleem, Amna; Ali, Zulfiqar; Bouzenada, Abdelmalek; Ditta, Allah; Atamurotov, Farruh; Mustafa, G. (Nuclear physics. B, 2025)
This study investigates the existence and stability of traversable wormhole (WH) solutions within the framework of Rastall Teleparallel Gravity. In this context, we focus on the impact of geometric constraints and energy conditions. Utilizing the class I embedding technique under the Karmarkar condition, we derive two novel static spherically symmetric WH solutions. In addition, these solutions are illustrated with distinct redshift functions, leading to corresponding shape functions that satisfy the Morris-Thorne criteria, ensuring asymptotic flatness and necessary throat conditions. The field equations, constructed within an anisotropic stress-energy tensor framework, are analyzed to evaluate the energy density, radial pressure, and tangential pressure distributions. A comprehensive graphical analysis tested the energy conditions, i.e., the null energy condition (NEC), weak energy condition (WEC), strong energy condition (SEC), and dominant energy condition (DEC). This shows the violations of the Null Energy Condition (NEC), confirming the presence of exotic matter necessary for sustaining WH structures. Both models exhibit regions where the energy density remains positive, while radial and tangential pressures violate classical energy conditions, reinforcing the theoretical expectations for the stability of the WH. Also, these results illustrated the compatibility of Rastall Teleparallel Gravity with traversable WH subjects and tested the intricate matter-geometry interplay in exotic spacetimes.